(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
This article describes the results of research on the production and storage of cornmeal grown in the northern regions of Uzbekistan. In this, scientifically based conclusions on the storage of processed corn flour products were made.